Reducing cardiovascular risk with immunomodulators: a randomised active comparator trial among patients with rheumatoid arthritis. Issue 3 (30th November 2022) - Solomon, Daniel H; Giles, Jon T; Liao, Katherine P; Ridker, Paul M; Rist, Pamela M; Glynn, Robert J; Broderick, Rachel; Lu, Fengxin; Murray, Meredith T; Vanni, Kathleen; Santacroce, Leah M; Abohashem, Shady; et al.
Abstract : Objective: Recent large-scale randomised trials demonstrate that immunomodulators reduce cardiovascular (CV) events among the general population. However, it is uncertain whether these effects apply to rheumatoid arthritis (RA) and if certain treatment strategies in RA reduce CV risk to a greater extent. Methods: Patients with active RA despite use of methotrexate were randomly assigned to addition of a tumour necrosis factor (TNF) inhibitor (TNFi) or addition of sulfasalazine and hydroxychloroquine (triple therapy) for 24 weeks. Baseline and follow-up 18 F-fluorodeoxyglucose-positron emission tomography/CT scans were assessed for change in arterial inflammation, an index of CV risk, measured as an arterial target-to-background ratio (TBR) in the carotid arteries and aorta. Results: 115 patients completed the protocol. The two treatment groups were well balanced with a median age of 58 years, 71% women, 57% seropositive and a baseline disease activity score in 28 joints of 4.8 (IQR 4.0, 5.6). Baseline TBR was similar across the two groups. Significant TBR reductions were observed in both groups—ΔTNFi: −0.24 (SD=0.51), Δtriple therapy: −0.19 (SD=0.51)—without difference between groups (difference in Δs: −0.02, 95% CI −0.19 to 0.15, p=0.79). While disease activity was significantly reduced across both treatment groups, there was no association with change in TBR (β=0.04, 95% CI −0.03 to 0.10). Conclusion: We found that addition of either a TNFi or triple therapy resulted in clinically important improvements in vascular inflammation. However, the addition of a TNFi did not reduce arterial inflammation more than triple therapy. Trial registration number: NCT02374021 .